Effects of Wilting and Lactobacillus plantarum Addition on the Fermentation Quality and Microbial Community of Moringa oleifera Leaf Silage - Wang, Yi; Wang, Cheng; Zhou, Wei; Yang, Fu-yu; Chen, Xiao-yang; Zhang, Qing (Frontiers in Microbiology, 2018)
The objective of this study was to evaluate the effects of wilting and Lactobacillus plantarum (LP) addition on the silage fermentation quality and microbial community of Moringa oleifera Lam. leaf silage. Unwilted (direct-cut) or wilted M. oleifera leaves were prepared either with or without LP (1.0×106 cfu/g) followed by either 60 or 120 days of ensiling, leading to eight treatment groups. The results showed that lactic acid was the dominant fermentation product, and no butyric acid was detected for any of the treatments. Higher acetic acid and propionic acid were detected during the fermentation of wilted silage compared to unwilted silage. Although NH3-N content increased after wilting, the content was far below 10% of the dry matter (DM). In addition, higher pH was observed after 120 days of ensiling compared to 60 days. Wilting also influenced the bacterial community structure. Lactobacillus was the most dominant genus in unwilted samples while Enterobacteriales, Weissella and Pantoea were the most dominant genera in wilted samples. Furthermore, the relative abundance of undesirable microorganisms was far below that of lactic acid bacteria in all treatments. In summary, wilting had significant effects on fermentation quality, and it was shown that M. oleifera leaves can undergo quality ensiling directly without the addition of LP.